Structuring Risk Assessment Process with Tallying in Aviation Safety Management. Issue 3 (2nd October 2019) - Uyar, Tevfik
ABSTRACT: One of the bounded rationality approaches is fast-and-frugal heuristics framework which is demarcating between risk and uncertainty concepts. The risk approach of the ICAO Safety Management System is completely based on the "risk" concept only and it recommends a risk assessment method not considering that some events can be described as uncertainty rather than risk because of insufficient data. Uncertainty conditions are complex and not-calculable events so the risk evaluation process may be error-prone due to the subjectivity of experts. This paper suggests using "tallying checklists" which are based on unit weight additive linear model, for making the probability and severity value assignments more consistent. Moreover, two checklists were created for a business jet operator and the twenty recent risk assessments of the operator were re-evaluated by using these checklists.